Hukum Syuro’ dalam Sistem Pemerintahan Islam: Shuro Law 'in the Islamic Government System - Zaini, Muhibuddin (Yayasan Pendidikan Islam Almatani, 2022)
Abstrak Islam agama yang sangat banyak dianut umat manusia didunia, Pew Research Center (PRC) menurut hasil risetnya, diperkirakan tahun 2070 Islam akan dianut oleh kebanyakan penduduk dunia dan penentu masa depan peradaban dunia. yang mengakibatkan akan terjadi transformasi sistem pemerintahan dunia melaksanakan roda pemerintahan menggunakan sistem pemerintahan islam dengan ketetapan Hukum Syuro’.Penelitian ini bertujuan mengetahui bagaimanakah Hukum Syuro’ dalam Sistem Pemerintahan Islam. Metode yang digunakan tercakup dalam penelitian hukum normatif. Hasil Penelitian menemukan bahwa dalam Sistem Pemerintahan Islam hukum Syuro’ tidak bisa lepas dari ajaran islam, sehingga Al-Qur’an dan hadis menjadi dasar hukum pemerintahan dan pemerintah. syuro’ memiliki karakter hukum bersifat wajib, bersifat pilihan, bersifat mengikat atau keterkaitan.Penulis menyarankan dalam konteks mengimplementasikan Hukum Syuro’ terhadap sistem pemerintahan Islam, diperlukan suatu ketaatan dan kesadaran dari umat Islam terhadap keputusan yang dikeluarkan oleh pemerintah melalui hasil Syuro’, sehingga Hukum yang ditetapkan menjadi bersifat wajib dan mengikat tanpa ada bersifat pilihan. Abstract Islam is very much embraced the human race in the world, one of the institutes in the United States were named Pew Research Center (PRC) argues through his research, Islam was about to become the religion professed by the majority of the world's population, which is estimated established in 2070. interpret Islam determining the future of world civilization which resulted in the magnitude of the change in the world government system carrying out the wheels of government through an Islamic government system with the provisions of theLaw Syuro’. This study focuses on discussing how theLaw is Syuro’ in the Islamic Government System, which aims to find out how theLaw is Syuro' in the Islamic Government System. The method used in this research is covered in normative legal research. With special specifications on the study of documentation, collecting data and documents needed, namely citing, reviewing, and adapting material from books (literature) or literature searches that have to do with the problems discussed, both in the form of books, papers and articles. articles and other scientific writings that are considered representative. The type of research used is descriptive using a Conceptual Approach and a Historical Approach. The results of the study found that in the Islamic Government System, thelaw Syuro' cannot be separated from Islamic teachings, so that the Qur'an and hadith become the legal basis for Islamic government, for a government to exercise its authority. according to experts and scholars, '' law Syuro’ has a legal character based on its nature, some are mandatory, optional, binding or related.